2007
DOI: 10.1111/j.1365-246x.2006.03223.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and genesis of slow-spreading ridges-seabed scattering and seismic imaging within the oceanic crust

Abstract: SUMMARY A grid of 32 across‐axis and five axis‐parallel multichannel seismic (MCS) reflection profiles were acquired at an axial volcanic ridge (AVR) segment at 57° 45′N, 32° 35′W on the slow‐spreading Reykjanes Ridge, Mid‐Atlantic Ridge, to determine the along‐axis variation and geometry of the axial magmatic system and to investigate the relationship between magma chamber structure, the along‐axis continuity and segmentation of melt supply to the crust, the development of faulting and the thickness of oceani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 93 publications
(168 reference statements)
0
17
0
Order By: Relevance
“…It also shows that the main fault terraces are separated by relatively unfaulted regions and that the seabed topography is asymmetric about the ridge axis. In addition, Topping (2002) and Peirce et al (2005), interpreting a grid of multichannel seismic reflection profiles acquired across the RAMESSES AVR, show that there is a distinct asymmetry in the faulting pattern with terraces separated at 2–5 km (200 000–500 000 yr) intervals which also correspond to periods of enhanced magmatism as evidenced by a correspondingly thicker extrusive layer within the upper crust. These observations, in the context of Thatcher & Hill's (1995) study, lend further support to cyclic rather continuous accretion and tectonism.…”
Section: Discussionmentioning
confidence: 99%
“…It also shows that the main fault terraces are separated by relatively unfaulted regions and that the seabed topography is asymmetric about the ridge axis. In addition, Topping (2002) and Peirce et al (2005), interpreting a grid of multichannel seismic reflection profiles acquired across the RAMESSES AVR, show that there is a distinct asymmetry in the faulting pattern with terraces separated at 2–5 km (200 000–500 000 yr) intervals which also correspond to periods of enhanced magmatism as evidenced by a correspondingly thicker extrusive layer within the upper crust. These observations, in the context of Thatcher & Hill's (1995) study, lend further support to cyclic rather continuous accretion and tectonism.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Tectonic lineations, mapped from GLORIA sidescan data [EEZ-Scan 84 Scientific Staff, 1986], are primarily oriented parallel or orthogonal to the Juan de Fuca Ridge axis (Figure 3b). Oblique lineations east of the survey area are interpreted as the trace of an inner pseudofault produced by ridge propagation that intersects the BTF at the saddle between the West and East Blanco Depressions [Peirce et al, 2007], Galapagos Ridge [Blacic et al, 2004], Juan de Fuca Ridge [Canales et al, 2005;Van Ark et al, 2007], Southeast Indian Ridge [Baran et al, 2005], and East Pacific Rise [Carbotte et al, 1997[Carbotte et al, , 2000Harding et al, 1993;Kent et al, 1994]. Lava thicknesses at tectonic windows are from studies at the Blanco Transform [Juteau et al, 1995;Karson et al, 2002b;Tivey et al, 1998], Hess Deep [Francheteau et al, 1990[Francheteau et al, , 1992Karson et al, 1992Karson et al, , 2002a, Pito Deep [Francheteau et al, 1994;Karson, 2005;Morgan et al, 2005], and Endeavor Deep (minimum thickness as sheeted dike complex may not be exposed) .…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…More recent seismic reflection studies have revealed evidence for crustal melt lenses or bodies beneath slow spreading centers. The Reykjanes Axial Melt Experiment: Structural Synthesis from Electromagnetics and Seismics at 57°45′N [e.g., Sinha et al , ; Peirce et al , ] revealed a seismic reflector 2.5–3 km beneath the seafloor on the Reykjanes Ridge underlain by a larger low‐velocity zone interpreted as a magma chamber that could contain up to 20% melt. Subsequently, the Seismic Study for Monitoring of the Mid‐Atlantic Ridge (SISMOMAR) seismic reflection experiment imaged a bright crustal reflector beneath the central volcano of the Lucky Strike segment of the MAR, interpreted as the roof a magma chamber [ Singh et al , ].…”
Section: Introductionmentioning
confidence: 99%